A resin composition and its application, semiconductor device and its preparation method

By chemically connecting the resin composition containing at least 3 alkoxy groups to the surface of the patterned film, the problem of uneven shrinkage of the patterned film in the prior art is solved, and a moderately uniform size is achieved Shrinkage and pattern quality improvement.

CN119060601BActive Publication Date: 2025-02-07ZHUHAI CORNERSTONE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411477210.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The crosslinking reaction between the macromolecular crosslinking agent and the surface of the patterned film in existing graphic miniaturized materials causes the size shrinkage of the patterned film to be too large and uneven, affecting the pattern quality, especially under the requirements of high-resolution patterning. Graphic bridge problem.

Method used

Provided is a resin composition, including a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent is an organosilane containing at least 3 alkoxy groups in the structure, and the resin includes a first repeating unit and a second repeating unit in the structure. The side chain of the first repeating unit has at least one of hydroxyl and carboxyl groups for chemical connection with the surface of the patterned film.

Benefits of technology

By using this resin composition, the patterned film can be moderately uniformly shrinked in size, reducing the probability of pattern adhesion, ensuring uniformity of pattern size, and meeting the requirements of high-resolution patterning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119060601B_ABST
    Figure CN119060601B_ABST
Patent Text Reader

Abstract

The present application embodiment provides a resin composition and its application, a semiconductor device and its preparation method. The resin composition can be arranged on the surface of a patterned film, and it includes a resin, a coupling agent and a non-aqueous organic solvent, and the coupling agent includes an organosilane containing at least 3 alkoxy groups in the structure; the structure of the resin includes a first repeating unit and a second repeating unit, the side chain of the first repeating unit has at least one of a hydroxyl group and a carboxyl group, the second repeating unit does not contain a hydroxyl group or a carboxyl group, and the molar ratio of the first repeating unit in all repeating units of the resin is 30%-80%. The above-mentioned resin composition can be used as a pattern shrinking material to achieve a moderate and uniform reduction in the pattern spacing of the patterned film, meeting the requirements of the semiconductor field for high-resolution patterning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of patterning technology, and specifically to a resin composition and application thereof, a semiconductor device and a preparation method thereof. Background Art

[0002] As the integration of semiconductor integrated circuits continues to increase, the requirements for the critical dimension (CD) of the chip pattern structure are also continuously reduced, the exposure wavelength used in the patterning process is getting shorter and shorter, and the cost of exposure equipment is also increasing. Without introducing new high-cost exposure equipment, achieving pattern shrinkage of patterned thin films on substrates for manufacturing integrated circuits can improve the resolution of the functional layer pattern obtained thereby and significantly reduce manufacturing costs.

[0003] Among them, graphic miniaturization materials are often used to coat the surface of patterned films, which usually contain resins and macromolecular crosslinking agents. Under heating conditions, the macromolecular crosslinking agent can crosslink and cure the resin with carboxyl groups on the surface of the patterned film, thereby increasing the film thickness and graphic sidewalls of the patterned film, and reducing the size of through holes or line gaps in the patterned film, thereby forming a finer pattern. However, the crosslinking reaction between the macromolecular crosslinking agent and the surface of the patterned film in the existing graphic miniaturization materials usually causes the size of the patterned film to shrink too much and shrink unevenly, which may cause graphic bridging problems under the high-resolution patterning requirements of advanced nodes, affecting the pattern quality. Summary of the invention

[0004] In view of this, the embodiments of the present application provide a resin composition and its application, a semiconductor device and its preparation method. The resin composition can make the patterned film have an appropriate and uniform dimensional shrinkage to meet the requirements of high-resolution patterning in the field of semiconductor devices.

[0005] Specifically, the first aspect of an embodiment of the present application provides a resin composition for being set on the surface of a patterned film, the resin composition comprising a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent comprises an organosilane having at least 3 alkoxy groups in its structure; the structure of the resin comprises a first repeating unit and a second repeating unit, the side chain of the first repeating unit has at least one of a hydroxyl group and a carboxyl group, the second repeating unit does not contain a hydroxyl group or a carboxyl group, and the molar proportion of the first repeating unit in all repeating units of the resin is 30%-80%.

[0006] The resin composition is coated on the surface of the patterned film. Under heating conditions, the bridging effect of the organic silane coupling agent can be used to achieve chemical connection between the central silicon atom and the resin in the resin composition and the specific reactive groups (such as carboxyl, hydroxyl, etc.) on the surface of the patterned film. After removing the resin and coupling agent not connected to the surface of the patterned film, the spacing distance between the patterns in the patterned film can be appropriately reduced, the probability of pattern adhesion is reduced, and the uniformity of the pattern size is ensured, which can meet the requirements of high-resolution patterning.

[0007] In some embodiments of the present application, the organosilane comprises an orthosilicate having a chemical formula of Si(OR)4, wherein each R is independently selected from substituted or unsubstituted C 1-6 Alkyl orthosilicate has a strong coupling ability, and its use can better achieve the chemical connection between the resin in the resin composition and the patterned film surface with carboxyl and / or hydroxyl groups.

[0008] In some embodiments of the present application, the coupling agent further comprises one or more of titanate, zirconate, aluminate, aluminozirconate coupling agent, and aluminum-titanium composite coupling agent. These coupling agents are small molecule organic metal ester coupling agents, which can play a similar role as the above-mentioned organic silane in bridging the resin and the patterned film surface.

[0009] In the embodiment of the present application, the mass of the coupling agent is 1%-30% of the mass of the resin. In this way, the resin composition has a suitable content of coupling agent to ensure that a certain amount of resin can be connected to the surface of the patterned film to effectively thicken the patterned film without causing material waste of the coupling agent.

[0010] In the embodiment of the present application, in the resin composition, the total mass proportion of the coupling agent and the resin is 0.5wt%-5wt%. This can ensure that the graphic sidewall of the patterned film coated with the resin composition can be effectively thickened without causing waste of the resin composition.

[0011] In the embodiment of the present application, the weight average molecular weight of the resin is in the range of 1000-20000. This can ensure that the resin has high solubility in the above-mentioned resin composition, and the resin has an appropriate number of first repeating units that can be chemically bonded with the coupling agent to effectively thicken the patterned film. In some embodiments, the weight average molecular weight of the resin is in the range of 4000-10000.

[0012] In an embodiment of the present application, the first repeating unit includes one or more of a styrene repeating unit, an acrylate repeating unit, and an acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on a side chain.

[0013] In an embodiment of the present application, the second repeating unit includes at least one of a styrene repeating unit, an acrylate repeating unit, and a methacrylate repeating unit that does not contain a hydroxyl group and a carboxyl group.

[0014] In the embodiment of the present application, the non-aqueous organic solvent includes one or more of an alcohol solvent and an ether solvent. These non-aqueous solvents are not likely to dissolve and damage the patterned film in contact with the resin composition, and can make the above-mentioned resin and coupling agent dissolve well therein.

[0015] The second aspect of the embodiment of the present application provides the use of the resin composition as described in the first aspect of the embodiment of the present application in reducing the critical dimension of the pattern. The application can specifically reduce the pattern spacing of the patterned film. With the patterned film with reduced pattern spacing, a functional layer pattern with a smaller critical dimension and higher resolution can be obtained, thereby obtaining a semiconductor device with a higher degree of integration.

[0016] A third aspect of the embodiments of the present application provides a method for preparing a semiconductor device, comprising:

[0017] (1) Providing a substrate having a patterned film on its surface; the surface of the patterned film having at least one of a hydroxyl group and a carboxyl group;

[0018] (2) applying the resin composition described in the first aspect of the embodiment of the present application to the surface of the patterned film to form a resin film, and heating the resin film to react with the portion of the resin film in contact with the patterned film;

[0019] (3) The unreacted resin film is removed by a cleaning solution to obtain a fine patterned film with reduced pattern spacing on the substrate.

[0020] The preparation method of the above-mentioned semiconductor device, by adopting the above-mentioned resin composition of the embodiment of the present application as the pattern shrinkage material, can achieve a moderate reduction in the pattern spacing of the formed patterned film, obtain a fine pattern with a smaller critical dimension at a lower cost, and ensure that the defects of the obtained pattern are small, which is conducive to the development of ultra-high integration of semiconductor devices.

[0021] In some embodiments of the present application, after obtaining a fine patterned film with reduced pattern spacing in step (3), the method may further include: transferring the pattern of the fine patterned film to a substrate to obtain a patterned substrate. Further, after obtaining the patterned substrate, the method may further include: forming a structure required for a semiconductor device on the patterned substrate.

[0022] The embodiment of the present application also provides a semiconductor device, which is manufactured using the manufacturing method described in the third aspect of the embodiment of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram showing the use of the resin composition of the present application to reduce the pattern spacing of a patterned film.

[0024] Figure 2 A scanning electron microscope top view of the contact hole pattern template used in the present application is shown.

[0025] Figure 3 A scanning electron microscope top view of the line pattern template used in this application is shown. DETAILED DESCRIPTION

[0026] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0027] In advanced semiconductor manufacturing processes, the patterning process generally includes the following steps: (1) coating a patterning composition (such as a chemically amplified photoresist including a base resin and a photoacid generator) on a substrate to form a patterned material film layer; (2) selectively exposing the patterned material film layer through an exposure source through a mask with a predetermined pattern, causing the photoacid generator in the exposure area to decompose and generate acid; in the baking process after exposure, the photoacid catalyzes the deprotection of the acid-labile protecting groups in the base resin in the exposure area, thereby increasing the polarity of the base resin in the exposure area, thereby producing a difference in the solubility of the developer between the exposure area and the unexposed area; (3) after exposure and baking, the patterned material film layer is developed with a developer, leaving a patterned film having the same or opposite pattern as the mask on the substrate, and the substrate can be selectively etched using the patterned film as a mask. Among them, if the exposed area of ​​the patterned material is removed by the developer (such as an aqueous solution of tetramethylammonium hydroxide) during development, the development can be called "positive development", and the photoresist pattern left on the substrate is a positive pattern, which is basically the same as the pattern of the exposure mask; if the unexposed area of ​​the patterned material is removed by the developer (such as an organic solvent such as n-butyl acetate) during development, the development can be called "negative development", and the photoresist pattern left on the substrate is a negative pattern, which is basically complementary to the pattern of the exposure mask.

[0028] Regardless of whether it is positive development or negative development, the pattern surface of the above-mentioned patterned film left on the substrate has functional groups such as carboxyl and / or hydroxyl groups generated by the deprotection of the acid-labile protective groups (generally, the positive pattern only has these functional groups on the pattern surface, and the negative pattern has these functional groups inside and on the surface), and these functional groups provide reaction sites that can be used by the pattern miniaturization material. Common pattern miniaturization materials usually contain resins and macromolecular crosslinking agents. The pattern miniaturization material is coated on the surface of the above-mentioned patterned film. Under heating conditions, the crosslinking agent in the composition can cause the resin to undergo a crosslinking and curing reaction with the carboxyl and / or hydroxyl groups on the surface of the patterned film, so that the pattern of the patterned film becomes wider. After removing the pattern miniaturization material that has not been crosslinked and cured with the patterned film, a patterned film with a shrunk pattern spacing (such as a reduced line gap, a reduced through-hole size, etc.) is obtained. The resolution of the deposited material pattern (such as metal interconnection lines, trench filling structures) obtained by filling the pattern gap, or the functional layer pattern obtained by etching with it as a mask is greater than the pattern obtained based on the initial patterned film.

[0029] However, the cross-linking reaction between the macromolecular cross-linking agent in the existing graphic miniaturization material and the surface of the patterned film usually causes a large size shrinkage of the patterned film. For the initial patterned film with a high resolution, too large a size shrinkage may cause problems such as pattern bridging, thereby reducing the quality of the pattern. In order to solve this technical problem, the embodiment of the present application provides a resin composition that can be used as a graphic miniaturization material, and the small molecule coupling agent therein can achieve an appropriate degree of size shrinkage of the patterned film and ensure the uniformity of the graphic size to meet the requirements of high-resolution patterning.

[0030] An embodiment of the present application provides a resin composition for being arranged on the surface of a patterned film, wherein the resin composition comprises a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent comprises an organosilane having at least three alkoxy groups in its structure; the structure of the resin comprises a first repeating unit and a second repeating unit, the side chain of the first repeating unit has at least one of a hydroxyl group and a carboxyl group, and the second repeating unit does not contain a hydroxyl group or a carboxyl group; and the molar proportion of the first repeating unit in all the repeating units of the resin is 30%-80%.

[0031] In the resin composition, an organosilane containing at least three alkoxy groups in its structure is used as a coupling agent, which has a central silicon atom and multiple water-decomposable groups (substituted or unsubstituted alkoxy groups). Under heating conditions, the Si-OH converted from the alkoxy groups in the organosilane can achieve chemical connection with the carboxyl and / or hydroxyl groups in the first repeating unit of the resin, and chemical connection with specific reactive groups (such as carboxyl, hydroxyl, etc.) on the surface of the patterned film, thereby forming a chemical thickening layer of a certain thickness on the surface of the patterned film. After removing the resin and coupling agent not connected to the surface of the patterned film, a patterned film with increased pattern sidewall thickness and reduced pattern spacing can be obtained. Moreover, since the above-mentioned organosilane is a small molecule substance rather than a high molecular polymer, the thickness of the chemical thickening layer formed by its coupling effect is thinner than the thickness of the thickening layer formed by means of a polymer cross-linking agent, and the shrinkage range of the pattern spacing of the patterned film is relatively small, thereby reducing the probability of pattern defects; more importantly, the distance between the resin and the surface layer of the patterned film is shortened by means of the coupling of the organosilane, so that the density of the above-mentioned chemical thickening layer is greater and the thickness is more uniform, thereby effectively improving the uniformity of the shrinkage range of the key dimensions of the patterned film.

[0032] In addition, the molar ratio of the first repeating unit containing hydroxyl and / or carboxyl groups in the above-mentioned resin is controlled to be 30%-80%. In this way, the solubility of the resin in non-aqueous organic solvents will not be reduced due to the molar ratio of the first repeating unit that can react with the coupling agent in the resin being too high, nor will the amount of resin connected to the surface of the patterned film be reduced due to the molar ratio of the first repeating unit being too low, and the patterned film cannot be effectively thickened.

[0033] Therefore, by coating the above-mentioned resin composition on the surface of the patterned film and undergoing certain treatments, the critical dimensions of the patterned film can be appropriately reduced, and the degree of size reduction is relatively uniform, which can better meet the requirements of high-resolution patterning, and a patterned film with a smaller critical dimension can be produced without replacing new exposure equipment with a shorter wavelength.

[0034] In the present application, the coupling agent includes an organosilane having at least three alkoxy groups in its structure. The three alkoxy groups are connected to the same silicon atom. The organosilane is not a polymer and may have one or more silicon atoms in its structure. The alkoxy group may be substituted or unsubstituted. Among them, the substituent in the substituted alkoxy group may include at least one of a halogen atom, an alkoxy group, an aryl group, an amine group, etc.

[0035] In some embodiments of the present application, the above-mentioned organosilane includes an orthosilicate with a chemical formula of Si(OR)4, wherein each R is independently selected from substituted or unsubstituted C 1-6 Accordingly, the above-mentioned -OR group can be referred to as a substituted or unsubstituted C 1-6Alkoxy. Orthosilicates containing four -OR groups have strong coupling ability, which can be used to achieve the connection between the resin in the resin composition and the surface of the patterned film, and better meet the needs of establishing a stable chemical thickening layer of appropriate thickness on the surface of the patterned film.

[0036] For the substituted alkyl group, the above carbon number of 1-6 refers to the alkyl group before substitution, and the carbon number can be 1, 2, 3, 4, 5 or 6. The substituent in the substituted alkyl group can include one or more of halogen atoms, alkoxy groups, aryl groups, and amine groups. The halogen atoms can include one or more of fluorine, chlorine, bromine, and iodine. An exemplary amine group can be -N(CH2CH2OH). The carbon number of the alkoxy group can be 1-6, for example, 1, 2, 3, 4, 5 or 6. The aryl group can be, for example, phenyl, or naphthyl. In some possible embodiments, the substituted alkyl group can be replaced by C 1-4 Alkoxy substituted C 1-6 Alkyl, or benzyl (-CH2C6H5, also known as benzyl). 1-4 The alkoxy group can be specifically methoxy, ethoxy, n-propoxy, or n-butoxy, etc. In some embodiments, each occurrence of R is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, 2-methoxyethyl (-CH2CH2OCH3), and benzyl.

[0037] In some other embodiments of the present application, the silane may include a silane coupling agent with a chemical formula of Y-Si(OR)3, where Y represents an organic functional group and R is defined as above. Exemplary Y may include one of an alkyl group, a phenyl group, a vinyl group, a (meth)acryloxy group, an epoxy group, and an amine group.

[0038] The following takes orthosilicate with the chemical formula Si(OR)4 as an example to illustrate the coupling effect between the above-mentioned organosilane and the resin in the above-mentioned resin composition or the surface of the patterned film.

[0039] The alkoxy group -OR connected to the Si atom in Si(OR)4 is converted into -OH when it meets water (the water can come from the air or the moisture released by the patterned film carrying the above resin composition under heating conditions). Under heating conditions, the Si-OH of adjacent molecules dehydrates and condenses to form a low-polysiloxane containing Si-OH. The remaining Si-OH group can form a chemical bond with the -OH in the resin or the -OH on the surface of the patterned film through dehydration condensation (such as through -Si-O-bonding), or Si-OH can form a chemical bond with the -OH in the resin or the -COOH on the surface of the patterned film (such as through -Si-OC(=O)-bonding), so that the central atom Si in the orthosilicate can be used to achieve chemical bonding with the surface of the patterned film and the resin at the same time. In addition, since the resin and the surface of the patterned film are bridged by chemical bonds containing Si atoms, the thickness of the above chemical thickening layer is relatively small, uniform and dense, which is conducive to obtaining a high-quality patterned film with moderate and uniform shrinkage of the pattern spacing.

[0040] In some embodiments of the present application, the coupling agent further comprises one or more organic metal ester coupling agents selected from titanate, zirconate, aluminate, aluminozirconate coupling agent, and aluminum-titanium composite coupling agent. The central metal atoms of titanate, zirconate, and aluminate are Ti, Zr, and Al, respectively. Titanate, zirconate, and aluminate may contain one or more metal atoms. The central metal atom of aluminozirconate includes Al and Zr. The central metal atom of an aluminum-titanium composite coupling agent includes Al and Ti.

[0041] The present application does not specifically limit the structure of the above titanate, zirconate, and aluminate, as long as the coupling effect can be achieved. In some possible embodiments, the chemical formula of the titanate includes TiL4. The chemical formula of the zirconate includes ZrL4. The chemical formula of the aluminate includes AlL3. Each L is independently selected from C 2-8 One or more of an alkoxy group (such as ethoxy, n-propoxy, isopropoxy, n-butoxy, 2-ethylhexyloxy, etc.), a benzyloxy group (ie, benzyloxy), a triethanolamine group, an acetylacetonate group, and an ethyl acetoacetate group.

[0042] Among them, the structure of 2-ethylhexyloxy is: The structure of the benzyloxy group is -O-CH2C6H5, which is a methoxy group substituted by a phenyl group. The structure of the triethanolamine group can be represented as , this group is essentially a substituted alkoxy group, that is, an ethoxy group substituted by N,N-bis(hydroxyethyl). Substituted or unsubstituted alkoxy groups can be converted into -OH under certain conditions, and the M-OH group (M represents the central metal atom) in the coupling agent is used to achieve the connection between it and the resin and patterned film with carboxyl and / or hydroxyl groups. Among them, the structure of the acetylacetonate group can be expressed as: The structure of ethyl acetoacetate can be expressed as: The acetylacetonate group or ethyl acetoacetate group can coordinate with metal atoms such as Ti, Zr, and Al. Under certain conditions, the acetylacetonate group or ethyl acetoacetate group can be replaced by -COOH or -OH in the above-mentioned resin or patterned film to achieve connection between the resin and the patterned film surface.

[0043] For titanate coupling agents, in some embodiments, they may include tetraethyl titanate (Ti(OCH2CH3)4), tetra-n-propyl titanate (Ti(OCH2CH2CH3)4), tetraisopropyl titanate (structural formula: ), tetrabutyl titanate (Ti(OCH2CH2CH2CH3)4), bis(acetylacetonato) diisopropyl titanate (structural formula is ), diisopropyl di(triethanolamine) titanate (structural formula: )、Hexabutoxy-μ-titanium(IV) oxide (structural formula is In some other embodiments, the titanate may also be hexabutoxy-μ-titanium (IV) oxide (structural formula: ).

[0044] As the zirconate coupling agent, one or more of tetraethyl zirconate, tetra-n-propyl titanate, tetraisopropyl zirconate, tetra-n-butyl zirconate and the like may be cited.

[0045] Examples of the aluminate coupling agent include triethyl aluminate, triisopropyl aluminate, tributyl aluminate, tribenzyl aluminate, aluminum triacetylacetonate, , bis(acetylacetonato)isopropylaluminate , (acetylacetonato) diisopropylaluminate , (ethyl acetoacetate) diisopropoxyaluminate One or more of the above.

[0046] In some embodiments of the present application, in the above-mentioned resin composition, the mass of the coupling agent is 1%-30% of the mass of the resin. It can be ensured that the above-mentioned resin composition has a suitable content of coupling agent to ensure that it can connect a certain amount of resin to the surface of the patterned film to effectively thicken the patterned film without causing material waste of the coupling agent. It should be noted that the mass of the coupling agent here refers to the sum of the masses of the above-mentioned organosilane and the organometallic ester coupling agent. If the above-mentioned resin composition does not contain an organometallic ester coupling agent, the mass of the coupling agent here only refers to the total mass of the above-mentioned organosilane. Specifically, the mass of the coupling agent can be 2%, 5%, 8%, 10%, 12%, 15%, 16%, 12%, 15%, 16%, 18%, 20%, 22%, 25%, or 28% of the mass of the resin. In some embodiments, the mass of the above-mentioned coupling agent can be 10%-25% of the mass of the resin.

[0047] In some embodiments of the present application, in the above-mentioned resin composition, the total mass proportion of the coupling agent and the resin is 0.5-5wt%. The resin composition has a suitable solid content, which can ensure that after being coated on the patterned film and heated, the graphic sidewall of the patterned film can be effectively thickened, and the patterned film will not be wasted due to the limited degree of thickening required for the patterned film. Specifically, in the resin composition, the total mass proportion of the coupling agent and the resin can be 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 4.8wt%, etc.

[0048] The resin includes a copolymer having both the first repeating unit and the second repeating unit, wherein the first repeating unit accounts for 30-80% by mole of all repeating units in the copolymer. Specifically, the mole ratio may be 35%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 70%, 75% or 78%, etc. In addition, the resin may include one or more copolymers having different structures.

[0049] In the present application, the structures of the first repeating unit and the second repeating unit of the above resin are not particularly limited. In some embodiments of the present application, the first repeating unit includes one or more of a styrene repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain, an acrylate repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain, and an acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain.

[0050] In some cases, the styrene repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain can be represented by the structure shown in the following (I-1):

[0051] (Ⅰ-1)

[0052] Wherein, R1 is selected from a hydrogen atom (H) or a methyl group (-CH3); and Z contains at least one of -OH and -COOH.

[0053] In some embodiments, Z is -OH, -COOH, or a substituted alkyl group whose substituent includes at least one of -OH and -COOH. Wherein, when Z is the substituted alkyl group, -OH or -COOH is connected to the benzene ring in (I-1) through an alkylene group. The number of carbon atoms of the substituted alkyl group may be 1-6, specifically 1, 2, 3, 4, 5 or 6. In addition, the substituted alkyl group may also have other substituents other than -OH or -COOH, which is not limited in this application. Wherein, the substituted alkyl group may or may not contain a heteroatom linking group, such as one or more of an ether bond (-O-), a thioether bond (-S-), a carbonyl group (-C(=O)-), etc. Exemplarily, Z may be -CH2CH2OH, -CH2CH2COOH, -OCH2CH2OH, etc.

[0054] The acrylic acid ester repeating unit or acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on the side chain can be represented by the structure shown in the following (I-2):

[0055] (I-2)

[0056] Wherein, R2 is selected from a hydrogen atom or a methyl group; L1 is independently selected from *-COO-, or *-CONH- each time it appears, and the * end is connected to the main chain carbon atom of formula (Ⅰ-2); R3 is independently selected from a substituted alkyl or substituted aryl group including at least one of -OH and -COOH each time it appears.

[0057] Among them, when L1 in formula (Ⅰ-2) is *-COO-, the structure shown in formula (Ⅰ-2) is specifically an acrylic acid ester repeating unit (which can be an acrylic acid alkyl ester repeating unit or an acrylic acid aryl ester repeating unit) having at least one of a hydroxyl group and a carboxyl group in the side chain; when L1 in formula (Ⅰ-2) is *-CONH-, the structure shown in formula (Ⅰ-2) is an acrylamide repeating unit (which can be an aliphatic repeating unit or an aromatic acrylamide repeating unit) having at least one of a hydroxyl group and a carboxyl group in the side chain.

[0058] For R3, -OH or -COOH can be directly connected to a carbon atom in an alkyl or aryl group, or indirectly connected to a carbon atom in an alkyl or aryl group through other groups. For example, the substituent in the substituted alkyl group may specifically include -OH, -COOH, or an aryl group substituted by at least one of -OH and -COOH, and the substituent in the substituted aryl group may specifically include at least one of -OH, -COOH, an alkyl group or an alkoxy group substituted by at least one of -OH and -COOH. Among them, the number of carbon atoms of the substituted alkyl group may be 1-6, and further may be 1-4. The number of carbon atoms in the substituted aryl group may be 6-20, and further 6-10. The number of carbon atoms here may be compared to the unsubstituted alkyl or aryl group. In addition, the substituted alkyl or substituted aryl group may also have other substituents other than -OH or -COOH. Exemplary R3 may be -Ph-OH, -Ph-COOH, -Ph-CH2CH2COOH, -CH2CH2OH, or -CH2CH2-Ph-OH, etc.; Ph represents phenyl.

[0059] In some embodiments of the present application, the second repeating unit includes at least one of a styrene repeating unit, an acrylate repeating unit, and a methacrylate repeating unit that does not contain a hydroxyl group or a carboxyl group. That is, the second repeating unit includes one or more repeating units derived from a styrene substance, an acrylate, and a methacrylate that does not contain a hydroxyl group or a carboxyl group.

[0060] For example, the structure of the styrene repeating unit without hydroxyl group and carboxyl group can be expressed as: , Z' does not contain -OH, nor does it contain -COOH. For example, Z' can be selected from one or more of a hydrogen atom, a halogen atom, a halogenated or unsubstituted alkyl group, or an alkoxy group. Among them, when Z' on the benzene ring can be all hydrogen atoms, the above repeating unit is specifically a styrene repeating unit.

[0061] Among them, the structure of the acrylate repeating unit without hydroxyl and carboxyl groups can be expressed as: The structure of the methacrylate repeating unit without hydroxyl and carboxyl groups can be: , each R' does not contain -OH or -COOH. For example, R' is a substituted alkyl or unsubstituted alkyl group that does not contain a hydroxyl group or a carboxyl group. In some embodiments, R' may also be a substituted aryl or unsubstituted aryl group that does not contain a hydroxyl group or a carboxyl group.

[0062] In some embodiments of the present application, the weight average molecular weight M of the resin is w In the range of 1000-20000. Control the M of the resin that can react with the coupling agent wIn an appropriate range, it can be ensured that the number of the first repeating units in the resin that can be chemically bonded with the coupling agent is not too small, which is conducive to ensuring that the resin composition can effectively thicken the patterned film, and at the same time will not be affected by the M of the resin. w Too large will result in low solubility of the resin in the above composition. w It can be measured by gel permeation chromatography (GPC) using polystyrene as a standard.

[0063] Exemplarily, the M of the resin w 2000, 3000, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, 12000, 15000, 18000 or 19000, etc. In some possible embodiments, the weight average molecular weight M of the resin is w In the range of 4000-10000, this is more conducive to the resin having good solubility in non-aqueous organic solvents and having a moderately obvious thickening effect on the patterned film.

[0064] In the present application, the solvent in the above resin composition is a non-aqueous organic solvent to prevent the substituted or unsubstituted alkoxy groups in the above coupling agent molecular structure from being hydrolyzed before the resin composition is coated on the surface of the patterned film, thereby precipitating solid particles and affecting the film-forming effect.

[0065] In the embodiment of the present application, the non-aqueous organic solvent in the above-mentioned resin composition may include one or more of an alcohol solvent and an ether solvent. These solvents are more conducive to the above-mentioned coupling agent and the resin with a reactive group that can act on the coupling agent to be dissolved and stably present therein, and it is not easy to dissolve the patterned film in contact with the resin composition. Among them, the alcohol solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, 4-methyl-2-pentanol, etc. The ether solvent may include one or more of n-butyl ether, diisoamyl ether, dipropylene glycol dimethyl ether, etc.

[0066] The embodiments of the present application also provide the use of the above-mentioned resin composition of the embodiments of the present application in reducing the critical dimension of a pattern.

[0067] The application is specifically to reduce the pattern spacing distance of the patterned film (specifically the photoresist pattern) during the preparation process of the semiconductor device. It can also be said that the resin composition is specifically used as a pattern shrinking material. With the patterned film with moderately and uniformly reduced pattern spacing, a semiconductor device with a pattern having a smaller pattern critical dimension and a higher pattern resolution can be prepared.

[0068] In the preparation process of semiconductor devices, the above resin composition can be used as a pattern shrinking material, which is arranged on the surface of a patterned film formed by a patterning process on a substrate. After heat treatment, a part of the resin composition material near the interface of the patterned film reacts with the surface of the patterned film to form a chemical thickening layer, thereby increasing the thickness and width of the pattern. After removing the unreacted resin composition material, a fine patterned film with a smaller and more uniform pattern spacing than the initial patterned film is formed. For details, please refer to the present application Figure 1 A schematic diagram showing the use of the resin composition of an embodiment of the present application to reduce the pattern spacing of a patterned film.

[0069] Wherein, for a patterned film having a contact hole pattern, the reduction of the critical dimension may refer to the reduction of the hole diameter. For a patterned film having a line pattern, the reduction of the critical dimension may refer to the reduction of the line spacing.

[0070] The embodiment of the present application also provides a method for preparing a semiconductor device. The method for preparing a semiconductor device may include the following steps S01, S02 and S03.

[0071] Step S01, such as Figure 1 As shown in (a), a substrate 10 having a patterned film 20 on its surface is provided, and the surface of the patterned film 20 has at least one of a hydroxyl group and a carboxyl group.

[0072] In the embodiment of the present application, the patterned film 20 is formed by a patterning process, and the patterning process generally includes steps such as coating a patterned composition, exposing, baking, and developing. The patterned film 20 includes but is not limited to being formed by patterning techniques such as ArF lithography. The resolution of the patterned film 20 formed by these patterning techniques is already high, and it is more meaningful to perform graphic miniaturization on it. A patterned film with a smaller critical dimension can be obtained at a lower cost without replacing expensive new exposure equipment. Optionally, the thickness of the patterned film 20 formed by these patterning techniques is in the range of 20nm-200nm. This can ensure that the graphics have a suitable aspect ratio and are not prone to collapse.

[0073] In some embodiments of the present application, the patterned film 20 may be a photoresist pattern, and may further be a chemically amplified photoresist pattern. The chemically amplified photoresist may include a base resin and a photoacid generator. Since the patterned film 20 is a film having a certain pattern formed by a patterning process (that is, the chemically amplified photoresist has been exposed and developed, and the acid-labile groups have been deprotected in the exposed area), the surface of the patterned film 20 may have carboxyl groups (-COOH) or hydroxyl groups (-OH), with carboxyl groups being the majority. In addition, in some cases, the surface of the patterned film 20 may also have hydroxyl groups derived from other repeating units in the base resin other than the acid-labile repeating units.

[0074] The substrate 10 can be selected according to specific needs, for example, it can be a silicon wafer, or a silicon wafer covered by other coatings. The coatings can include one or more of an anti-reflective coating, an epitaxial layer, a metal layer, a dielectric layer (such as SiO2, or Si3N4), etc.

[0075] Step S02, such as Figure 1 As shown in (b), the resin composition of the embodiment of the present application is coated on the surface of the patterned film 20 to form a resin film 30, and then heated to react with the portion of the resin film 30 that contacts the patterned film 20.

[0076] Wherein, the coating method includes but is not limited to spin coating, dip coating, brush coating, etc. In the above-mentioned coating process, the above-mentioned resin composition is not only located on the surface of the patterned film 20, but also located at the pattern gap of the patterned film 20. Wherein, the thickness of the resin film 30 is preferably to fill the pattern gap (including pores) of the patterned film 20 and thicken by 10-30%. This is conducive to ensuring the formation of a chemical thickening layer of appropriate thickness, while not affecting the convenient removal of unreacted resin composition materials. Wherein, the coating thickness of the resin film 30 can be adjusted according to the amount of solvent added to the resin composition. Generally, the higher the solid content of the above-mentioned resin composition, the thicker the thickness of the resin film 30 formed by coating. Optionally, the solid content in the above-mentioned resin composition is 0.5-5wt%. While being able to effectively thicken the graphic sidewalls of the patterned film 20, it will not cause material waste.

[0077] In step S02, the heating may be heating the substrate 10 with the patterned film 20 and the resin film 30. During the heating process, a reaction occurs between the patterned film 20 and the resin film 30 at the contact interface. Figure 1As shown in (c), a chemical thickening layer 40 of a certain thickness is formed on the surface of the patterned film 20. The chemical thickening layer 40 is mainly formed by chemically bridging the resin in the resin film 30 and the surface of the patterned film 20 with the help of the small molecule coupling agent in the resin film 30 under heating conditions. The formation mechanism of the chemical thickening layer 40 can be found in the explanation of the previous text of this application.

[0078] In the embodiment of the present application, the heating temperature may be 100-180°C, for example, 110°C, 120°C, 130°C, 150°C, 160°C, or 170°C. The heating time may be 30 seconds to 180 seconds, for example, 45s, 60s, 90s, 120s, etc. Controlling the heating temperature may control the reaction rate of the coupling agent in the resin film 30 with the surface active groups of the patterned film 20 and the resin in the resin film 30, thereby controlling the thickness of the chemical thickening layer 40 and the amount of pattern shrinkage. Controlling the heating time may also control the thickness of the chemical thickening layer 40.

[0079] Step S03, after removing the unreacted resin film 30 with a cleaning solution, a fine patterned film 20' with reduced pattern spacing is obtained on the substrate 10, such as Figure 1 As shown in (d).

[0080] The above-mentioned "unreacted resin film 30" specifically refers to the resin film 30 that is not grafted to the surface of the patterned film 20. This part of the resin film can be washed away by the cleaning solution, while the part of the resin film grafted to the surface of the patterned film 20 (i.e., the chemical thickening layer 40) can be retained without being washed away by the cleaning solution. Among them, the fine patterned film 20' can include the initial patterned film 20 and the chemical thickening layer 40 connected thereto. The presence of the chemical thickening layer 40 increases the thickness and pattern width of the fine patterned film 20', so that the interval between adjacent patterns of the fine patterned film 20' becomes smaller.

[0081] In the embodiment of the present application, the cleaning liquid may include an alkaline aqueous solution or an organic solvent. The cleaning liquid may be applied to the substrate 10 by spin coating, spraying, dipping, etc. Among them, the alkali in the alkaline aqueous solution may include one or more of tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), etc. The organic solvent may include, but is not limited to, one or more of alcohol solvents (such as ethanol, isopropanol, ethylene glycol, propylene glycol, 1-pentanol, 4-methyl-2-pentanol, etc.), ester solvents (such as n-butyl acetate, propylene glycol monomethyl ether acetate, ethyl acetate, ethyl lactate, butyrolactone, etc.), ether solvents (such as propylene glycol monomethyl ether, propylene glycol ethyl ether, n-butyl ether, diisoamyl ether, dipropylene glycol dimethyl ether, anisole, etc.). The patterned film 20 formed by the patterning process has strong tolerance to these cleaning liquids, and when they are used to remove the unreacted resin film 30, the patterned film 20 below will not be damaged.

[0082] Optionally, the pattern pitch of the fine patterned film 20' in step S03 is reduced by 3-15 nm compared to the pattern pitch of the patterned film 20 in step S01. Figure 1 That is, Δd' is 3-15nm smaller than Δd. That is, the resin composition provided in the present application can reduce the pattern spacing of the patterned film 20 by 3-15nm. For the patterned film 20 with a higher pattern resolution, the resin composition provided in the present application has a suitable shrinkage degree for the pattern spacing, and adjacent patterns will not stick together.

[0083] After the above step S03, a fine patterned film 20' is formed on the substrate 10. The narrower pattern spacing of the fine patterned film 20' can be used to define smaller features than when only the patterned film 20 is used. In some embodiments, the pattern of the fine patterned film 20' can be transferred to the substrate to obtain a patterned substrate. The patterned substrate can be used for the preparation of semiconductor devices such as chips to improve the preparation accuracy and quality of the device.

[0084] After the above step S03, other functional layers can be prepared. For example, after the above step S03, a metal material can be deposited in the gap to form a metal pattern layer. The fine patterned film 20' with a narrower gap can also be used as a mask to perform high-precision etching on the substrate 10, and the pattern thereon can be transferred to the substrate 10 by etching to further realize the preparation of other coatings.

[0085] The method for preparing the above-mentioned semiconductor device provided in the embodiment of the present application, by adopting the resin composition of the embodiment of the present application as the pattern shrinkage material, can achieve a moderate and uniform reduction in the pattern spacing distance of the formed patterned film, obtain a fine pattern with a smaller critical dimension at a lower cost, and ensure that the obtained pattern has high clarity and small defects, which is conducive to the high-integration and high-precision development of semiconductor processes.

[0086] The embodiment of the present application also provides a semiconductor device, which is obtained by using the above-mentioned semiconductor preparation method of the embodiment of the present application.

[0087] The semiconductor device may include but is not limited to a chip, etc. It is understandable that the semiconductor device product usually does not contain the fine patterned film 20'.

[0088] The embodiments of the present application are further described below with reference to a plurality of embodiments.

[0089] Example 1

[0090] (I) Preparation of resin:

[0091] 8.00 g of N-p-hydroxyphenyl acrylamide, 4.94 g of 4-tert-butoxystyrene and 2.42 g of initiator dimethyl azobisisobutyrate were dissolved in 46 g of isopropanol solvent, and the oxygen in the system was removed by three freeze-thaw cycles, and then reacted at a reflux temperature of 83°C for 6 hours. The obtained reactant was vacuum dried to remove the solvent, 46 g of ethyl acetate was added and stirred to dissolve, and then 5 times the volume of n-heptane was added for precipitation. After suction filtration, the precipitation operation was repeated once, and the solid was collected. The obtained solid was vacuum dried at 60°C to obtain a weight average molecular weight M w The resin P1 has a molecular weight of 5808 and a molecular weight distribution index PDI of 2.45.

[0092] The preparation process of resin P1 is as follows:

[0093]

[0094] From the hydrogen nuclear magnetic resonance spectrum of the resin P1, it was found that the molar ratio of the repeating unit derived from N-p-hydroxyphenylacrylamide to the repeating unit derived from 4-tert-butoxystyrene (ie, m:n) was 3:2.

[0095] (II) Preparation of resin composition:

[0096] 2.6 g of resin P1 was dissolved in 97 g of n-butanol, and 0.4 g of tetraethyl orthosilicate was added to the resulting solution. After sufficient stirring to dissolve, the solution was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a resin composition solution, which was recorded as F1.

[0097] (III) Preparation of pattern template 1:

[0098] The bottom anti-reflective coating material is coated on a silicon wafer substrate and heated on a hot plate at 205°C for 60 seconds to form a 30nm thick bottom anti-reflective coating. Then, a chemically amplified photoresist is coated on the bottom anti-reflective coating and heated on a hot plate at 110°C for 60 seconds to form a 120nm thick photoresist film layer. The photoresist film layer is exposed through a mask using an ArF exposure device, and baked on a hot plate at 95°C for 60 seconds after exposure. Thereafter, an aqueous solution of tetramethylammonium hydroxide with a concentration of 2.38wt% is used for immersion development for 60 seconds to remove the exposed portion, and then washed with deionized water for 10 seconds to form a hexagonally arranged contact hole pattern template P-CH (which can be referred to as pattern template 1) with a pore size of 130.44nm and a pore spacing of 345nm. The scanning electron microscope top view is shown as follows Figure 2 shown.

[0099] (IV) Resin composition for graphic miniaturization:

[0100] The resin composition F1 was spin-coated onto the contact hole pattern template P-CH at a rotation speed of 1500 rpm to form a resin film, and heated on a hot plate at 150° C. for 60 seconds to react with the portion of the resin film in contact with the surface of the pattern template. The substrate was then immersed in a tetramethylammonium hydroxide aqueous solution with a concentration of 2.38 wt % for 30 seconds to remove the resin film material not connected to the surface of the pattern film, and washed in water for 10 seconds to obtain a contact hole pattern after pore size shrinkage, and the average pore size, pore size standard deviation, and pore size shrinkage of the contact hole pattern were measured, and the results are summarized in the following Table 1.

[0101] Comparative Example 1

[0102] Preparation of the resin composition: 2.6 g of resin P1 was dissolved in 97 g of n-butanol, and 0.4 g of a commercial crosslinking agent (methylated hexahydroxymethyl melamine resin) was added. After sufficient stirring to dissolve, the mixture was filtered through a polytetrafluoroethylene filter with a pore size of 0.2 μm to obtain a resin composition solution.

[0103] The resin composition provided in Comparative Example 1 was coated on the contact hole pattern template PCH, and heated on a hot plate at 120°C for 60 seconds, then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove materials not connected to the surface of the contact hole pattern template, and then washed in water for 10 seconds to obtain a contact hole pattern with shrunken aperture. The average aperture, aperture standard deviation and aperture shrinkage of the contact hole pattern were measured, and the results are also shown in Table 1 below.

[0104] Table 1

[0105]

[0106] Note: The pore size shrinkage refers to the difference between the average pore size of the contact holes obtained after the resin composition undergoes pattern shrinkage and the average pore size in the initial contact hole pattern template.

[0107] It can be seen from Table 1 that after the contact hole pattern template is subjected to pattern shrinkage using the resin composition F1 of Example 1 at a heating temperature of 150°C, the average pore size shrinkage of the contact holes is 8.77nm, which is much smaller than the pore size shrinkage caused by the resin composition of Comparative Example 1 using a polymer resin as a crosslinking agent at the same heating temperature, greatly reducing the probability of deformation of the contact hole shape. Moreover, more importantly, the pore size standard deviation of the contact holes in the contact hole pattern obtained by using the resin composition of Example 1 is also much lower than that of Comparative Example 1, which indicates that the pore size uniformity has been significantly improved.

[0108] Example 2

[0109] (I) Preparation of resin:

[0110] 8.00 g of hydroquinone monomethacrylate, 4.87 g of 4-tert-butoxystyrene and 2.23 g of dimethyl azobisisobutyrate were dissolved in 46 g of isopropanol solvent, and the oxygen in the system was removed by three freeze-thaw cycles, and then the reaction was carried out at a reflux temperature of 83 ° C for 6 hours. After the obtained reactant was vacuum dried to remove the solvent, 46 g of ethyl acetate was added and stirred to dissolve, and then 5 times the volume of n-heptane was added for precipitation. After suction filtration, the precipitation operation was repeated once, and the solid was collected. The obtained solid was vacuum dried at 60 ° C to obtain a weight average molecular weight M w The resin P2 has a molecular weight of 7025 and a molecular weight distribution index PDI of 2.25. According to the nuclear magnetic resonance test, the molar ratio of the repeating unit derived from hydroquinone monomethacrylate to the repeating unit derived from 4-tert-butoxystyrene in the resin P2 is 3:2.

[0111] The preparation process of resin P2 is as follows:

[0112]

[0113] (II) Preparation of resin composition:

[0114] 2.6 g of resin P2 was dissolved in 97 g of n-butanol, and 0.4 g of tetraethyl orthosilicate was added to the resulting solution. After sufficient stirring to dissolve, the solution was filtered through a polytetrafluoroethylene filter with a pore size of 0.2 μm to obtain a resin composition solution, which was recorded as F2.

[0115] (III) Preparation of pattern template 2:

[0116] The bottom anti-reflective coating material is coated on a silicon wafer substrate and heated on a hot plate at 205°C for 60 seconds to form a 30nm thick bottom anti-reflective coating. Then, a chemically amplified photoresist is coated on the bottom anti-reflective coating and heated on a hot plate at 90°C for 60 seconds to form a 90nm thick photoresist film layer. The photoresist film layer is exposed through a mask using an ArF exposure device, and baked on a hot plate at 95°C for 60 seconds after exposure. After that, it is immersed in n-butyl acetate for 30 seconds to remove the exposed part, and washed with deionized water for 10 seconds to obtain a line pattern template N-LS (referred to as pattern template 2) with a line width of 54.66nm and a spacing of 125nm. The scanning electron microscope top view of the line pattern template is shown as follows. Figure 3 shown.

[0117] (IV) Resin composition for graphic miniaturization:

[0118] The resin composition F2 was spin-coated onto the line pattern template N-LS at a rotation speed of 1500 rpm to form a resin film, and heated on hot plates at 120°C and 135°C for 60 seconds, respectively, to react with the portion of the resin film in contact with the surface of the pattern template. Then, it was immersed in ethanol for 30 seconds to remove the resin film material not connected to the surface of the pattern film, thereby obtaining a line pattern with a shrunk line spacing. The line width and line spacing shrinkage of the pattern were measured from these figures, and the results are summarized in the following Table 2.

[0119] Table 2

[0120]

[0121] It can be seen from Table 2 that after the line pattern template was subjected to pattern shrinkage at heating temperatures of 120°C and 135°C using the resin composition F2 of Example 2, the pattern line width was appropriately increased and the line spacing was appropriately shrunk accordingly.

[0122] Example 3

[0123] A resin composition, which is different from the resin composition F1 in Example 1 in that 0.4 g of tetraethyl orthosilicate in Example 1 is replaced by 0.2 g of tetraisopropyl titanate and 0.2 g of tetraethyl orthosilicate.

[0124] Referring to the method described in the above-mentioned Example 1, the resin compositions provided in Example 3 were respectively coated on the contact hole pattern template PCH and heated on a hot plate at 150°C for 60 seconds, followed by immersion in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove the resin composition material not connected to the surface of the pattern template, and then rinsed in water for 10 seconds to obtain a contact hole pattern with a shrunken aperture.

[0125] Among them, in the contact hole pattern with the above-mentioned pore size shrinkage, the average pore size of the contact holes is measured to be 123.62nm, the pore size standard deviation is 3.27nm, and the pore size shrinkage is 6.82nm. The pore size shrinkage is much smaller than the effect brought by the resin composition of comparative example 1 using a polymer resin as a cross-linking agent, and the pore size uniformity of the shrunk contact holes is also high (reflected by a lower pore size standard deviation).

[0126] Example 4

[0127] A resin composition, which differs from the resin composition F1 of Example 1 in that the amounts of monomers used in preparing the resin are changed so that in the obtained resin, the molar ratio of repeating units derived from N-p-hydroxyphenylacrylamide to repeating units derived from 4-tert-butoxystyrene is 3:7.

[0128] Example 5

[0129] A resin composition, which differs from the resin composition F1 of Example 1 in that the amounts of monomers used in preparing the resin are changed so that in the obtained resin, the molar ratio of repeating units derived from N-p-hydroxyphenylacrylamide to repeating units derived from 4-tert-butoxystyrene is 8:2.

[0130] Example 6

[0131] A resin composition is prepared, comprising: dissolving 2.8 g of resin P1 in 97 g of n-butanol, adding 0.2 g of tetraethyl orthosilicate, stirring and dissolving the mixture, and filtering the mixture through a polytetrafluoroethylene filter with a pore size of 0.2 μm to obtain a resin composition. In the resin composition of Example 6, the mass of the coupling agent tetraethyl orthosilicate is 7% of the mass of the resin P1.

[0132] Example 7

[0133] A resin composition is prepared, comprising: dissolving 2.4 g of resin P1 in 97 g of n-butanol, adding 0.6 g of tetraethyl orthosilicate, stirring and dissolving the mixture, and filtering the mixture through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a resin composition. In the resin composition of Example 7, the mass of the coupling agent tetraethyl orthosilicate is 25% of the mass of the resin P1.

[0134] Referring to the method described in the above-mentioned Example 1, the resin compositions provided in Examples 4-7 were respectively coated on the contact hole pattern template PCH and heated on a hot plate at 150°C for 60 seconds, and then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove the resin composition material not connected to the surface of the pattern template, and then washed in water for 10 seconds to obtain a contact hole pattern with pore size shrinkage, and the average pore size, pore size standard deviation and pore size shrinkage amount were measured. The results are summarized in the following Table 3.

[0135] Table 3

[0136]

[0137] From the comparison between Examples 4, 5, and 1 in Table 3, it can be seen that when the solid content and coupling agent in the resin composition remain unchanged, changing the molar ratio of the active repeating units of the resin in the resin composition of the embodiment of the present application within a certain range can also have the effect of appropriately and uniformly shrinking the pore size in the contact hole pattern.

[0138] From the comparison among Examples 6, 7 and 1 in Table 3, it can be learned that, when the solid content of the resin composition remains unchanged, the relative content of the coupling agent and the resin is changed within a certain range, the shrinkage amount of the aperture in the contact hole pattern can be regulated.

[0139] The above only expresses the exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims.

[0140] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.

[0141] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0142] In the description of this application, unless otherwise specified, the meaning of "multiple" refers to greater than or equal to two. "At least one" refers to one or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0143] In addition, the numerical range represented by "-" in this application refers to the range that includes the numerical values ​​recorded before and after "-" as the minimum and maximum values, respectively. In this application, expressions about parameter ranges, such as "greater than or equal to (≥)", "less than or equal to (≤)", "above...", and "below..." all include the number itself. The numerical values ​​and numerical ranges involved in the embodiments of this application are approximate values. Due to the influence of manufacturing processes / testing methods, etc., there may be a certain range of errors, which can be considered negligible by those skilled in the art.

Claims

1. A resin composition for reducing the critical dimension of a pattern of a patterned film, characterized in that: The resin composition comprises a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent comprises an organosilane having at least three alkoxy groups in its structure; the structure of the resin comprises a first repeating unit and a second repeating unit, the side chain of the first repeating unit has at least one of a hydroxyl group and a carboxyl group, the second repeating unit does not contain a hydroxyl group or a carboxyl group, and the molar proportion of the first repeating unit in all the repeating units of the resin is 30%-80%, and the mass of the coupling agent is 1%-30% of the mass of the resin.

2. The resin composition according to claim 1, characterized in that The organosilane comprises an orthosilicate of formula Si(OR)4, wherein each R is independently selected from substituted or unsubstituted C 1-6 alkyl.

3. The resin composition according to claim 1, characterized in that The coupling agent also includes one or more of titanate, zirconate, aluminate, aluminozirconate coupling agent, and aluminum-titanium composite coupling agent.

4. The resin composition according to claim 3, characterized in that The chemical formula of the titanate includes TiL4, the chemical formula of the zirconate includes ZrL4, and the chemical formula of the aluminate includes AlL3, each L being independently selected from C 2-8 One of an alkoxy group, a benzyloxy group, a triethanolamine group, an acetylacetonate group, and an ethyl acetoacetate group.

5. The resin composition according to any one of claims 1 to 4, characterized in that In the resin composition, the total weight ratio of the coupling agent and the resin is 0.5-5wt%.

6. The resin composition according to claim 1, characterized in that The first repeating unit includes one or more of a styrene repeating unit, an acrylate repeating unit, and an acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on a side chain.

7. The resin composition according to claim 1, characterized in that The second repeating unit includes at least one of a styrene repeating unit, an acrylate repeating unit, and a methacrylate repeating unit that does not contain a hydroxyl group or a carboxyl group.

8. The resin composition according to claim 1, characterized in that The weight average molecular weight of the resin is in the range of 1,000-20,000.

9. The resin composition according to claim 1, characterized in that The non-aqueous organic solvent includes one or more of an alcohol solvent and an ether solvent.

10. The resin composition according to claim 9, characterized in that The alcohol solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, and 4-methyl-2-pentanol; the ether solvent includes one or more of n-butyl ether, diisoamyl ether, and dipropylene glycol dimethyl ether.

11. Use of the resin composition according to any one of claims 1 to 10 in reducing the critical dimension of a pattern.

12. A method for preparing a semiconductor device, characterized in that: include: (1) Providing a substrate having a patterned thin film; The surface of the patterned film has at least one of a hydroxyl group and a carboxyl group; (2) applying the resin composition according to any one of claims 1 to 11 to the surface of the patterned film to form a resin film, and performing a heat treatment so that the resin film reacts with the portion in contact with the patterned film; (3) The unreacted resin film is removed by a cleaning solution to obtain a fine patterned film with reduced pattern spacing on the substrate.

13. The preparation method according to claim 12, characterized in that: The pattern spacing of the fine patterned film in step (3) is reduced by 3-15 nm compared with the patterned film in step (1).

14. A semiconductor device, characterized in that: The method is prepared according to any one of claims 12 to 13.

Citation Information

Patent Citations

  • Positive photosensitive resin composition and method for preparing cured pattern

    CN116027636A

  • Pattern forming process and shrink agent

    US20160124313A1